PUZZLE PLAY THERAPY WITH PARENTS AS A NON-PHARMACOLOGICAL INTERVENTION FOR PRESCHOOL CHILDREN'S ANXIETY DUE TO HOSPITALIZATION - Mela Agramadani; Indah Permatasari (Poltekkes Kemenkes Jakarta III, 2026)
Preschool children frequently experience anxiety during hospitalization due to unfamiliar environments, unpleasant medical procedures, and limited interaction with their parents. This anxiety may reduce children’s cooperation during treatment and negatively affect treatment outcomes if it is not properly managed. This study aimed to determine the effect of puzzle-playing therapy involving parental participation on anxiety levels among hospitalized preschool children. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 22 preschool-aged children admitted to Tarakan Regional General Hospital, Central Jakarta, Indonesia. Anxiety levels were assessed using the Face Image Scale (FIS) before and after the intervention. Puzzle-playing therapy was administered with parental involvement for approximately 15 minutes over two days. Univariate and bivariate analyses were conducted using the Wilcoxon test. The results showed that the median anxiety score decreased from 4 to 1 following the intervention. The Wilcoxon test indicated a statistically significant difference (p = .001). These findings demonstrate that puzzle-playing therapy involving parental participation effectively reduces anxiety among hospitalized preschool children.